Office gynecology a case-based approach - Chelmow, David; Karjane, Nicole; Ricciotti, Hope; Young, Amy E. (University Press House, 2019)
"The intent of this book is to help practitioners of women's health care, including OB/GYNs, Family Practitioners, and Internal Medicine Women's Health Specialists, with these many changes. The book is intended for physicians, trainees, nurse midwives, nurse practitioners, and physician's assistants. We chose 100 important ambulatory gynecology problems, and present them in a case based format. They are intended to be easy to read and suitable as a quick office reference for providers seeing similar patients. The book is meant to supplement the many other journals, electronic references, and textbooks available, but in a real-life format suitable for adult learners"...Provided by publisher